Biological Assessments of Encapsulated Pancreatic ß-Cells: Their Potential Transplantation in Diabetes - Mooranian, Armin; Negrulj, Rebecca; Jamieson, E.; Morahan, G.; Al-Salami, Hani (Springer New York LLC, 2016)
© 2016. Biomedical Engineering Society. Microencapsulation of pancreatic islets has been considered as a promising method for cell transplantation and diabetes treatment. However, in vivo trials to date have been hampered by fibrotic overgrowth and very limited to no success, long-term. Future success requires suitable microencapsulating method and possibly a simplified and suitable formulation which will produce a microcapsule that provides an immunobarrier, maintain full ß-cell functionality whilst also reducing the inflammatory processes that induce fibrosis. In multiple studies, we screened various formulations and microencapsulating methods, and obtained promising results using bile acid-based microcapsules containing ß-cells, in terms of cell functions and insulin release. Thus, this study aimed to refine further the microencapsulating method using a simple alginate-poly-l-ornithine formulation and test the effect of adding a promising bile acid, ursodeoxycholic acid (UDCA), on cell functions. Using Büchi concentric nozzle, viable NIT-1 cells were microencapsulated using alginate-poly-l-ornithine, with or without UDCA at a ratio of 1:1.2 or 1:1.2:4. Screening for nozzle temperature and nozzle-gelation bath distance was carried out to form best microcapsules. Microcapsules were cultured for 48 h and examined for size and surface morphology, chemical profiling and ß-cell viability. Culture supernatants were examined for insulin and inflammatory cytokines. When using 30 °C nozzle-temperature and 5 cm nozzle-gelation bath distance, in the presence of the bile acid, cell mitochondrial activities and insulin production were optimised. Under deployed microencapsulating method with nozzle-temperature of 30 °C and nozzle-gelation bath distance of 5 cm, the incorporation of the bile acid into the microcapsules resulted in enhanced ß-cell survival, function and improved overall biocompatibility supporting potential applications in transplantation.